Analysis of Heavy Metals Concentration in Tissues of Three Different Fish Species Included in Human Diet from Danube River - Milanov Đ. Raša (Sciendo, 2016)
The aim of this study was the investigation of water, sediments and fish tissues contamination with heavy metals. All samples were taken from the Danube River in Belgrade region, a location upstream from Batajnica. Concentrations of Cd, Hg and Pb in water samples were not detected, while concentrations of Zn, Fe, Cu and As were in the range of 0.004 - 0.330 mg L-1. Iron was the most deposited metal in sediment samples in contrast to water samples where all investigated metals were detected. For the purpose of heavy metals determination in fresh fish tissue, fifteen samples of three different fish species, silver carp (Hypophthalmichthys molitrix), common carp (Cyprinus carpio) and wels catfish (Silurus glanis) were collected. Concentrations of Pb, Cd, As and Hg were determined in the digestive tract, liver and muscle by absorption spectroscopy. The highest concentration of Pb was in the digestive tract in all three fish species, ranging from 0.036 to 1.518 μg g-1, while Cd was mostly deposited in the liver. Concentrations of As were in the range of 0.36 - 0.73 μg g-1 in Hypophthalmichthys molitrix, 0.013 - 0.18 μg g-1 in Cyprinus carpio and 0.003 - 0.005 μg g-1 in Silurus glanis tissues, while the content of Hg was equal in all tested tissues of carp. Concentrations of all metals were found to be present in the fish samples at different levels, but these values are under the maximum residual levels prescribed by the European Union (EU) and the maximum allowed concentrations (MAC) for Serbia, so the fish meat is acceptable for the human consumption.